The Potential of Indonesian Textbooks in Stimulating Students' Learning Activities - Huda, Miftakhul; Anjas Rusdiyanto Soleh; Nadia Zakiyyah; Safira Inayatul Maula; Siwi Nur Arifah; Retno Astri Ardaninggar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The use of verbal units in textbooks will be mapped out. Although textbooks are considered an essential source of information, aspects such as language that can stimulate student engagement, project-based tasks that support collaboration, and reflection and discussion in improving critical thinking skills should be considered. This study aims to identify the potential of Indonesian language textbooks to stimulate students' learning activities. The research method used is a qualitative approach with a case study method. The research sample was selected purposively, namely one Indonesian language textbook used in one of the secondary schools. Data were collected through observation, interviews, literature study, and document analysis. The instruments used were interviews and observation sheets. The results showed that textbooks can be an effective stimulus in stimulating students' learning activities. Textbooks can stimulate student activity by presenting exciting material, encouraging reflection and discussion, and providing project-based tasks. The selection of textbooks that suit learning needs is also essential. The compatibility between textbooks and students' level of thinking will facilitate students' understanding of the material and achieve learning objectives. Overall, Indonesian language textbooks have great potential to improve students' learning activities. Appropriate use of textbooks can motivate students, broaden their participation, and enhance learning achievement.